Blick über Wald auf Nain und Bucht mit Treibeis im Juli : [ca. 1900] (2001)
Black and white photograph of a view of Nain from the forested hill. Ice can be seen floating in the bay. The photograph was taken in July, circa 1900. Black and white photograph of a view of Nain from the forested hill. Ice can be seen floating in the bay. The photograph was taken in July, circa 1900.